Hygrometric assessment of internal relative humidity in concrete : practical application issues - Granja, José Luís Duarte (2014)
The use of embedded relative humidity (RH) sensors for assessing the internal humidity in concrete is widely spread, dully backed by existing standards. Even though the approaches adopted in the literature seem to have several differences between each other, few or none research works were found to focus on the comparison of performance of sensors and methods for RH measurement. In view of this, several sets of experiments comparing the performances of different sensors and monitoring procedures will be presented in this paper, discussing the main findings and providing recommendations for the strategies to be adopted in what concerns the measurement technique. The main points addressed in this work are: (i) comparisons between readily available systems for RH measurement in concrete, as well as custom measurement strategies reported in the literature; (ii) issues related to calibration procedures and re-calibration necessity; (iii) relevance of the existence of an interface porous material between the embedded sensor and the measurement spot in concrete; (iv) importance of the size of the embedment body into which the RH sensor is inserted; (v) equivalence of results obtained when the probe is constantly inserted into the embedment body, or placed inside it at discrete instants.